1985
DOI: 10.2343/geochemj.19.77
|View full text |Cite
|
Sign up to set email alerts
|

Deposition of anthropogenic sulfate and Pb-210 in the western North Pacific area.

Abstract: The monthly deposition rates of sodium, calcium, chloride, sulfate and Pb-210 from the atmosphere were measured at 12 stations in various parts of the Japanese Islands for two years. The deposition rates of sea salt particles were higher in the coastal region near the Sea of Japan in winter, demonstrating the fact that the strong winter monsoon produces many sea salt particles. Amounts of chloride, sulfate and calcium in excess of the sea salt component were always observed. The rather uniform annual depositio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
16
1

Year Published

1985
1985
2012
2012

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(19 citation statements)
references
References 16 publications
(20 reference statements)
2
16
1
Order By: Relevance
“…These values lie in the range of 166-383 Bq/m 2 (1-2.3 dpm/cm2), in which higher values are found in the areas facing the Sea of Japan. Although the total deposition (833-1054Bq/m 2) of 21~ found here was 2-3 times higher than the highest value (383 Bq/m 2) found by TSUNOGAI et al 16 and YOKOTA, 17 we believe that the resuspension of soil particles during the deposition sampling will not contribute more than 15-20%.…”
Section: Seasonal Variations and Deposition Velocitiescontrasting
confidence: 39%
See 1 more Smart Citation
“…These values lie in the range of 166-383 Bq/m 2 (1-2.3 dpm/cm2), in which higher values are found in the areas facing the Sea of Japan. Although the total deposition (833-1054Bq/m 2) of 21~ found here was 2-3 times higher than the highest value (383 Bq/m 2) found by TSUNOGAI et al 16 and YOKOTA, 17 we believe that the resuspension of soil particles during the deposition sampling will not contribute more than 15-20%.…”
Section: Seasonal Variations and Deposition Velocitiescontrasting
confidence: 39%
“…Thus, about half of the total deposition of 21~ and 7Be per year occurs during winter. This cyclic trend of seasonal variations has been observed especially in heavy snowfall areas facing the Sea of Japan 14 and is due to the addition of 21~ transported from the continent and the effective scavenging of aerosols in air by snowfall during winter l5 21 TSUNOGAI et al 16 and YOKOTA 17 have reported on the annual deposition rates of 21~ at various locations in Japan. These values lie in the range of 166-383 Bq/m 2 (1-2.3 dpm/cm2), in which higher values are found in the areas facing the Sea of Japan.…”
Section: Seasonal Variations and Deposition Velocitiesmentioning
confidence: 99%
“…In the regions along the Sea of Japan, strong northwest wind prevails in winter. Thus, the large deposition rate of sodium in winter is due to the transport of sea salt particles from the Sea of Japan (Tsunogai et al, 1985). As shown in Fig.…”
Section: Introductionmentioning
confidence: 97%
“…These facts strongly suggest that the large increases in sulfate deposition rates in winter at Toyama and Wajima were not caused by the local discharge, but by transport of the anthropogenic sulfur dioxide from the Asian continent with a strong northwest winter monsoon. The increases in sulfur deposition rate in winter have been ob served in various regions along the Sea of Japan (e.g., Tsunogai et al, 1985;Kitamura et al, 1991;Toriyama et al, 1991a;Yamaguchi et al, 1991). They could also be attributed to the long distance transport of sulfur dioxide from the Asian continent.…”
mentioning
confidence: 99%
“…[6] estimated the (AMAD) of 210 Pb of 0.53 μm and [7] 0.56 μm. 210 Pb has been extensively used to determine the mean residence time of atmospheric aerosols [8], to trace chemical compound that may have broadly similar source distributions, for example sulphur [9], and to study the transport of continental aerosols across the sea or into Polar Regions [10,11].…”
Section: Introductionmentioning
confidence: 99%